Examination of the short-range structure of molten salts: ThF4, UF4, and related alkali actinide fluoride systems. Issue 18 (4th May 2021) - Ocádiz-Flores, J. A.; Gheribi, A. E.; Vlieland, J.; de Haas, D.; Dardenne, K.; Rothe, J.; Konings, R. J. M.; Smith, A. L.
Abstract : The short-range structures of molten alkali actinide fluoride salts were studied using in situ EXAFS combined with molecular dynamics simulations. Abstract : The short-range structures of LiF–ThF4, NaF–AnF4, KF–AnF4, and Cs–AnF4 (An = Th, U), were probed using in situ high temperature Extended X-ray Absorption Fine Structure (EXAFS) spectroscopy. Signally, the EXAFS spectra of pure molten ThF4 and UF4 were measured for the first time. The data were interpreted with the aid of Molecular Dynamics (MD) and standard fitting of the EXAFS equation. As in related studies, a speciation distribution dominated by [AnF x ] 4− x ( x = 7, 8, 9) coordination complexes was observed. The average coordination number was found to decrease with the increasing size of the alkali cation, and increase with AnF4 content. An average coordination number close to 6, which had not been detected before in melts of alkali actinide fluorides, was seen when CsF was used as solvent.